From Crystalline to Amorphous Germania Bilayer Films at the Atomic Scale: Preparation and Characterization - Lewandowski, Adrián L. (Angew Chem Int Ed Engl, 2019)
A new two‐dimensional (2D) germanium dioxide film has been prepared. The film consists of interconnected germania tetrahedral units forming a bilayer structure, weakly coupled to the supporting Pt(111) metal‐substrate. Density functional theory calculations predict a stable structure of 558‐membered rings for germania films, while for silica films 6‐membered rings are preferred. By varying the preparation conditions the degree of order in the germania films is tuned. Crystalline, intermediate ordered and purely amorphous film structures are resolved by analysing scanning tunnelling microscopy images.